2011
DOI: 10.1002/smi.1396
|View full text |Cite
|
Sign up to set email alerts
|

Building Personal and Professional Resources of Resilience and Agility in the Healthcare Workplace

Abstract: This article describes the rationale, implementation and results of a pilot study evaluating the personal and organizational impact of an educational intervention on the stress of health team members. The compelling imperative for the project was to find a positive and effective way to address the documented stress levels of healthcare workers. Pilot study of oncology staff (n=29) and healthcare leaders (n=15) exploring the impact of a positive coping approach on Personal and Organizational Quality Assessment-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
134
0
3

Year Published

2014
2014
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 133 publications
(143 citation statements)
references
References 28 publications
4
134
0
3
Order By: Relevance
“…11 The hand therapist might choose to address the following reflections to support the artistry of caring: "What are the unique attributes of this client and this situation? It is a good idea to confirm or validate verbally what you understand from the client's expression.…”
Section: Common Pitfalls and How To Avoid Themmentioning
confidence: 99%
“…11 The hand therapist might choose to address the following reflections to support the artistry of caring: "What are the unique attributes of this client and this situation? It is a good idea to confirm or validate verbally what you understand from the client's expression.…”
Section: Common Pitfalls and How To Avoid Themmentioning
confidence: 99%
“…Though the concept originated in manufacturing sector, it was found beneficial in service sectors as well; especially in healthcare sector [4]. Many studies and found that agile practices can help the healthcare organizations to meet the service demand which changes quickly and unpredictably and at the same time retain the competitive advantage over other players in the market [5, 6]. In addition, resilience and agility were found to be extremely crucial in healthcare [5].…”
Section: Introductionmentioning
confidence: 99%
“…Many studies and found that agile practices can help the healthcare organizations to meet the service demand which changes quickly and unpredictably and at the same time retain the competitive advantage over other players in the market [5, 6]. In addition, resilience and agility were found to be extremely crucial in healthcare [5]. Many studies in literature discussed how agility capabilities can help up-gradation of healthcare service quality [6].…”
Section: Introductionmentioning
confidence: 99%
“…Research shows that employer-sponsored wellness programs contribute to the overall health and well-being of their employees, improve employee productivity and retention, and reduce absenteeism and health care costs [1][2]. Studies explore various ways of promoting positive strategies for coping and building individual and organizational resilience, which are considered important factors that influence the health and productivity of healthcare workers [3][4][5][6][7][8]. Resilience is defined as "the process of effectively negotiating, adapting to, or managing significant sources of stress or trauma" [9].…”
Section: Introductionmentioning
confidence: 99%